Couples: Case - Ginicola, M.M. (Critical Incidents in Integrating Spirituality into Counseling, 2015)
This chapter talks about Michael and Ethan's case study, where two people were involved in being in an interfaith relationship. The author's primary goal was to help each become empathic and to understand the other's position on coming out and being a public couple. A secondary goal was to increase their communication in articulating their feelings surrounding coming out officially. Working from an existential approach, the author encouraged them both to explore their meanings associated with religion, their families, and each other. He used the Emotionally Focused Couples Therapy (EFCT) approach, and insights of integrating sexual orientation and religious identities, spiritual interventions, and dealing with discrimination. Building on the strength-based model, the author identified positive assets that each brought to the relationship individually and in a partnership. Each was willing to develop a plan that represented a middle ground between their two positions. © 2015 by the American Counseling Association. All rights reserved.
Journal Abbreviation: Crit. Incid. in Integr. Spirit. into Couns.
Keywords: Discrimination; Emotionally Focused Couples Therapy; Homosexuality; Religious identities; Same-sex couples; Spiritual Interventions; dept.csp